THE TRANSFORMATIONAL LEADERSHIP AT ISLAMIC BOARDING SCHOOLS IN THE DIGITAL ERA - Nizma Armila; Vina Sopianingsih (Balai Diklat Keagamaan Bandung, 2022)
Most pesantren, especially in Java, are established on the initiative of Kyai. Kyai’s leadership style is more likely to be authoritarian/paternalistic. This paper research uses a descriptive approach qualitative type of Literature Review Study method to identify, evacuate and synthesize previous studies. The data obtained are parsed regularly in a descriptive analysis for its study nature. A normative sociological approach is also used to enrich the perspective. At the end of this article, a strong relationship between progress in pesantren and leaders who adopt transformative leadership styles is concluded. The transformative leadership styles need to be adopted by pesantren leaders in Indonesia, complemented by recommendations for kyais who intend to shift into transformative ones. Keywords: Islamic Boarding School; Transformational Leadership; Kyai